Chronic Diarrhea in Children - Begum, Fahmida; Nahid, Khan Lamia; Mazumder, Md Wahiduzzaman; Rukunuzzaman, Md; Karim, ASM Bazlul (Journal of Enam Medical College, 2021)
Chronic diarrhea (CD) is a common but challenging clinical scenario in pediatric medicine. It has several hundred disorders in the differential diagnosis and can create a complex situation for practitioners and families. Some of the disorders cause failure to thrive but some are not. This article focuses on important aetiologies of CD, their clinical features, diagnostic approach as well as treatment approaches. J Enam Med Col 2021; 11(2): 120-127